The Anthem guide to short fiction (Anthem Press, 2011)
"'The Anthem Guide to Short Fiction' contains 20 classic short stories by well-known and respected authors. Some of the stories included are rarely anthologized in the contemporary publishing market. Accordingly, the selection provides a fresh perspective on each author and his or her place in the literary canon. The guide also features individual biographical notes for each writer and a short introduction of his or her short story. Each story is followed by a critical 'Thinking about the Story' section, as well as incisive discussion questions formulated for students to respond to the text as a piece of literature. Similarly, the creative activities have been devised to stimulate critical and imaginative thinking in the reader. The aim of this text is to give student writers agency, as well as an understanding of authorship and the creative process. This guide also includes a concise glossary of literary terms designed for optimal and regular use"--